Intensification or expansion? A new approach to measuring agricultural change - Bloem, Jeffrey R.; Lundberg, Clark (VoxDev, 2025)
Drawing on a randomised controlled trial among rice farmers in Nigeria, we introduce a new method for linking village-level interventions with high-resolution earth observation data – which captures spatial variation in how new technologies spread and influence land use. While we find evidence that the adoption of improved fertiliser boosts agricultural productivity, the effects on tree canopy cover depend on the local landscape.